Corrosion-resistant part, preparation method thereof and plasma processing device

By using a method of combining a transparent yttrium-based sintered body with a conductive layer and drilling holes in semiconductor components, the problem of microparticle contamination during the etching process was solved, resulting in semiconductor components with high light transmittance and corrosion resistance, and improving the stability of the etching process and product quality.

CN121693015APending Publication Date: 2026-03-17ADVANCED MICRO FAB EQUIP INC CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411289546.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Microparticle contamination is easily generated during the etching process of existing semiconductor components. The main reasons include damage to the edge of the hole, difficulty in cleaning the hole, uneven coating growth, and light irradiation damage, which leads to a decline in product quality.

Method used

The component body is made of transparent yttrium-based sintered body, and a conductive layer is formed on its upper surface. Through-holes are formed by composite drilling to avoid the generation of microparticles during the subsequent coating process. The high light transmittance, corrosion resistance and mechanical properties of transparent yttrium-based sintered body are utilized to reduce defects.

Benefits of technology

It effectively avoids microparticle contamination, improves the corrosion resistance and optical transmittance of components, reduces defects caused by hole edge damage and uneven coating, and ensures the stability of the etching process and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121693015A_ABST
    Figure CN121693015A_ABST
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant part, a preparation method thereof and a plasma processing device. The preparation method comprises the following steps: providing a part body made of a transparent yttrium-based sintered body; performing surface conduction on the upper surface of the part body to form a conductive layer; and punching the part body subjected to surface conduction to form a hole channel penetrating through the part. Transparent yttrium-based powder is sintered into a transparent yttrium-based sintered body, the transparent yttrium-based sintered body is compounded with a conductive layer to prepare a conductive part body, and then the conductive part body is punched. Before and after punching, the surface of the part body and the inner walls of the holes are all transparent yttrium-based sintered bodies, so that film coating on the surface of the part body and the inner walls of the holes after punching is avoided, and then generation of microparticles is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor technology, specifically to a corrosion-resistant component, its preparation method, and a plasma treatment apparatus. Background Technology

[0002] In semiconductor manufacturing, etching equipment is commonly used to precisely remove specific materials from silicon wafers. In etching equipment, aluminum may be used for components that do not directly contact etching gases or chemicals, or for components that can be protected using coating techniques. For example, gas spray disks typically use aluminum as the substrate material, and a protective layer is coated onto the aluminum substrate using physical vapor deposition or atomic layer deposition to prevent corrosion of the gas spray disk by etching gases.

[0003] As semiconductor feature sizes shrink, the requirements for etching process stability, feature size accuracy, and etching morphology control become increasingly stringent. Simultaneously, the control of microparticle contamination in the production environment also becomes more stringent. When applying a protective layer using physical vapor deposition, incomplete protective layers may form at the holes in the gas spray disk, creating defects. These defective areas, due to uneven or incomplete protective layers, may lead to material instability, resulting in the generation of microparticles during etching. These microparticles can contaminate the silicon wafer, thus affecting product quality. Summary of the Invention

[0004] The purpose of this invention is to provide a corrosion-resistant component, its preparation method, and a plasma treatment device to overcome the defects of existing semiconductor components that are prone to microparticle contamination.

[0005] To achieve the above objectives, the present invention provides a method for preparing corrosion-resistant parts, comprising: providing a part body made of a transparent yttrium-based sintered body; performing surface conductivity on the upper surface of the part body to form a conductive layer; and drilling holes in the surface-conductive part body to form a through-hole in the part.

[0006] Optionally, the surface conductivity includes applying a metallic conductive layer to the upper surface of the component body.

[0007] Optionally, the surface conductivity includes implanting metal ions into the upper surface of the component body to form a metal conductive layer extending downward from the upper surface of the component body.

[0008] Optionally, the metal ions contain Al 3+ Ni 3+ and Ti 3+ At least one of them.

[0009] Optionally, the concentration of the metal ion implantation is 10E12 atoms / cm². 2 ~10E14 atoms / cm 2 .

[0010] Optionally, the thickness of the conductive layer is 500 nm to 1000 nm.

[0011] Optionally, the conductivity of the conductive layer is 10. -2 Ω / cm~10 -3 Ω / cm.

[0012] Optionally, the transparent yttrium-based sintered body comprises at least one of: transparent yttrium oxide sintered body, transparent yttrium fluoride sintered body, and transparent yttrium fluoride sintered body.

[0013] Optionally, the light transmittance of the transparent yttrium-based sintered body is not less than 95%.

[0014] Optionally, the surface roughness of the transparent yttrium-based sintered body is 0.05 μm to 0.1 μm.

[0015] Optionally, the method for preparing the transparent yttrium-based sintered body includes:

[0016] Mixing step: Take yttrium-based powder as a precursor and silica nanospheres as a sintering aid, and mix the yttrium-based powder and the silica nanospheres evenly;

[0017] Molding steps: The mixed yttrium-based powder and silica nanospheres are pressed to obtain a powder compact. The pressure is 100 MPa to 200 MPa and the pressing time is 24 to 48 hours.

[0018] Sintering step: The powder compact is sintered under vacuum using a laser as a heat source to obtain the transparent yttrium-based sintered body. The laser intensity is 100 W / cm². 2 ~200W / cm 2 The vacuum level in the vacuum environment is 10. -4 MPa ~ 10 -5 MPa, sintering time is 5h to 8h.

[0019] Optionally, in the mixing step, the grain size of the yttrium-based powder is 5 nm to 20 nm.

[0020] Optionally, in the mixing step, the mass ratio of the yttrium-based powder to the silica nanospheres is 0.05 wt% to 0.1 wt%.

[0021] Optionally, the transparent yttrium-based sintered body is selected from transparent yttrium-based ceramics.

[0022] Optionally, the density of the transparent yttrium-based ceramic is not less than 99%.

[0023] The present invention also provides a corrosion-resistant component, comprising at least:

[0024] The body of the component is made of transparent yttrium-based sintered material;

[0025] A conductive layer located on the upper surface of the component body;

[0026] A plurality of channels are provided through the conductive layer and the component body;

[0027] The light transmittance of the transparent yttrium-based sintered body is not less than 95%.

[0028] Optionally, the thickness of the conductive layer is 500 nm to 1000 nm.

[0029] Optionally, the diameter of the channel is 0.35mm to 0.37mm.

[0030] Optionally, the transparent yttrium-based sintered body comprises at least one of: transparent yttrium oxide sintered body, transparent yttrium fluoride sintered body, and transparent yttrium fluoride sintered body.

[0031] Optionally, the corrosion-resistant component includes at least one of the following: a gas spray disc, a constraint ring, and a grounding ring.

[0032] The present invention also provides a plasma processing apparatus, which includes at least the corrosion-resistant components described in any one of the above.

[0033] Optionally, the plasma processing device is an inductively coupled plasma etching device or a capacitively coupled plasma etching device.

[0034] Compared to the prior art, the beneficial effects of the present invention include at least the following:

[0035] (1) This invention utilizes transparent yttrium-based powder as a blank, directly sintering it to obtain a component body made of transparent yttrium-based sintered body. A conductive metal layer is applied to the upper surface of the component body, or an ion implantation is performed on the upper surface of the component body to form a conductive metal layer. The transparent yttrium-based sintered body and the conductive metal layer are then combined to prepare a conductive component body. Holes are then drilled into the conductive component body to form through-holes. After drilling, the inner walls of the holes are all transparent yttrium-based sintered body, which has excellent corrosion resistance. Therefore, it is unnecessary to apply a separate coating to the inner walls of the holes to form a corrosion-resistant coating, thus avoiding the generation of microparticles and defects.

[0036] (2) The transparent yttrium-based sintered body of the present invention has higher light transmittance and density than ordinary yttrium-based sintered bodies. In a plasma environment, ultraviolet or infrared light can penetrate the transparent yttrium-based sintered body and enter the metal conductive layer. The metal conductive layer can conduct the heat generated by ultraviolet and infrared light in a timely manner, avoiding radiation damage inside the semiconductor components. In addition, the transparent yttrium-based sintered body has strong mechanical properties, low coefficient of thermal expansion and strong corrosion resistance, which can greatly prevent the generation of microparticles in semiconductor components. Attached Figure Description

[0037] Figure 1 This is a flowchart of a method for preparing a corrosion-resistant component according to the present invention.

[0038] Figure 2 This is a partial cross-sectional view of a corrosion-resistant component before drilling, according to the present invention.

[0039] Figure 3 This is a partial cross-sectional view of a corrosion-resistant component after drilling, according to the present invention.

[0040] Figure 4 This is a schematic diagram of the structure of a capacitively coupled plasma etching apparatus provided in an embodiment of the present invention.

[0041] Figure 5 Scanning electron microscope (SEM) images of conductive transparent yttrium oxyfluoride ceramics provided for embodiments of the present invention and thermally sprayed yttrium oxyfluoride coatings provided for comparative examples:

[0042] Wherein, a represents the scanning electron microscope (SEM) microstructure of the conductive transparent yttrium oxyfluoride ceramic of the embodiment, and b represents the SEM microstructure of the thermally sprayed yttrium oxyfluoride coating of the comparative example.

[0043] Figure 6 Scanning electron microscope (SEM) images of the surface morphology of conductive transparent yttrium oxyfluoride ceramic provided for embodiments of the present invention and thermally sprayed yttrium oxyfluoride coating provided for comparative examples:

[0044] Wherein, a represents a scanning electron microscope (SEM) image of the conductive transparent yttrium oxyfluoride ceramic of the embodiment, and b represents a scanning electron microscope (SEM) image of the thermally sprayed yttrium oxyfluoride coating of the comparative example.

[0045] Figure 7 A comparison diagram of the etching rates of the etched surfaces of the conductive transparent yttrium oxyfluoride ceramic provided in the embodiments of the present invention and the thermally sprayed yttrium oxyfluoride coating provided in the comparative example.

[0046] Figure 8 X-ray diffraction pattern of conductive transparent yttrium fluoride ceramic provided for embodiments of the present invention.

[0047] Attached image labels:

[0048] Reaction chamber 1; base 2; substrate w; gas spray disk 3; radio frequency source 4; component body 31; conductive layer 32; hole 33; capacitively coupled plasma etching equipment 100. Detailed Implementation

[0049] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0050] In the description of this invention, it should be noted that the terms "upper," "lower," "left," "right," "vertical," "horizontal," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing the invention and for simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the invention. Furthermore, the terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.

[0051] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "joining" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal communication between two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.

[0052] It should be noted that the accompanying drawings are all in a very simplified form and use non-precise ratios, and are only used to facilitate and clarify the illustration of the embodiments of the present invention.

[0053] In the manufacturing process of semiconductor components, for some components with holes or complex geometries and requiring corrosion resistance, it is common practice to first drill holes in the semiconductor component blank, and then deposit a corrosion-resistant coating of a certain thickness on all surfaces and the inner walls of the holes. For example, the manufacturing method for the gas spray head of a plasma processing chamber generally includes the following steps: drilling several gas through holes from top to bottom on an aluminum alloy substrate using a drilling device; and depositing a corrosion-resistant coating (such as a yttrium oxide coating) of a certain thickness on the inner walls of the gas holes and on the aluminum alloy substrate. This method of drilling first and then coating is widely used in the manufacturing process of semiconductor components.

[0054] However, this method of drilling holes before coating is prone to microparticle contamination, mainly due to the following reasons:

[0055] (1) Coverage problem: When coating the inner wall of the hole of semiconductor components, especially at some corners of the hole, the coverage is usually required to be higher. However, the coating technology will produce some imperfect traces (i.e. defects) at these corners. Specifically, when depositing coating at the hole, due to the limitation of geometric structure, the coating may not be able to cover evenly, and deposition defects such as voids and cracks are easily formed at the edge of the hole. These defects may become the source of micro particles.

[0056] (2) Coating growth problem: For coating technology, chemical vapor deposition, physical vapor deposition, atomic layer deposition and other processes are usually used to deposit a thin film of a certain thickness on the surface of aluminum substrate. If some key process parameters (such as temperature, gas flow rate, gas concentration, vacuum degree, etc.) are not properly controlled during the process, micro particles may be generated.

[0057] (3) Photoradiation damage: In a plasma environment, the processing chamber usually contains ultraviolet and infrared light. Ultraviolet light has high energy and can directly break the chemical bonds of the coating material on the surface of semiconductor components, causing photochemical or thermal effects on the surface of the coating material, thus causing damage. Although infrared irradiation has lower photon energy, long-term infrared irradiation may cause the local temperature of the coating material on the surface of semiconductor components to rise, thereby causing thermal stress, thermal expansion or thermal fatigue, which may damage the coating.

[0058] (4) Insufficient cleanliness of the substrate surface: If the substrate is not sufficiently cleaned and treated before coating, residual organic matter, metal ions or other impurities may affect the adhesion of the coating layer, resulting in a decrease in coating quality.

[0059] Even with improvements to the aforementioned coating technology—such as optimizing the coating process on the inner walls of holes in semiconductor components, precisely controlling key process parameters during coating growth, improving the coating's radiation resistance, and enhancing the surface cleanliness of the substrate—it's still difficult to avoid microparticle contamination with the current technique of drilling holes before coating. This is mainly because:

[0060] (1) Hole edge damage: The hole edge of the aluminum alloy substrate may be damaged during the drilling process, resulting in microscopic defects, cracks or burrs. These damages may not be completely repaired during the subsequent coating deposition process, thus becoming a potential source of microparticle contamination.

[0061] (2) Difficulty in cleaning holes: After drilling, there may be processing debris or material particles inside the holes. Cleaning these particles inside the holes may be difficult, causing these particles to be wrapped in the coating or on the coating surface during the deposition process.

[0062] (3) Stress concentration: The edges of the holes after drilling may become areas of stress concentration. The coating may be more prone to cracking or peeling in these areas, resulting in microparticle contamination.

[0063] To address the aforementioned technical problems, this invention provides a method for preparing corrosion-resistant components, comprising: providing a component body made of a transparent yttrium-based sintered body; surface conductiveizing the upper surface of the component body to form a conductive layer; and drilling holes in the surface-conductive component body to form through-holes. This invention directly composites the semiconductor component blank made of a transparent yttrium-based sintered body with the conductive layer to form a conductive component body. Drilling holes in the component body then creates a dense, corrosion-resistant transparent yttrium-based sintered body on the inner walls of the holes, avoiding the need for coating the inner walls of the holes after drilling, thus significantly reducing the generation of microparticles and defects. Furthermore, the transparent yttrium-based sintered body possesses excellent optical, thermal, and corrosion-resistant properties, further reducing the generation of microparticles. Simultaneously, by ensuring the component body is a high-performance transparent yttrium-based sintered body before drilling, the deposition of a corrosion-resistant layer on its surface is also unnecessary.

[0064] like Figure 1 As shown, the present invention provides a method for preparing corrosion-resistant parts, comprising:

[0065] Step S1: Provide a component body made of a transparent yttrium-based sintered body.

[0066] Transparent yttrium-based sintered bodies are a special type of material, typically referring to yttrium oxide ceramics, such as transparent yttrium oxide (Y₂O₃) ceramics. In some embodiments, the transparent yttrium-based sintered body comprises at least one of transparent yttrium oxide sintered body, transparent yttrium fluoride sintered body, and transparent yttrium fluoride sintered body. When preparing corrosion-resistant parts, a transparent yttrium-based sintered body is first prepared. Taking transparent yttrium fluoride oxychloride (YOF) sintered body as an example, the preparation method of the transparent yttrium fluoride oxychloride sintered body includes:

[0067] Mixing step: Select YOF powder with a grain size of 5nm to 20nm as a precursor for transparent yttrium-based sintered body, and select silica nanospheres with a grain size of 5nm as a sintering aid. Mix the YOF powder and the silica nanospheres evenly; wherein, by mass ratio, the mass percentage of YOF powder to silica nanospheres is 0.05wt% to 0.1wt%, for example: 0.05wt%.

[0068] Molding steps: The mixed YOF powder and silica nanospheres are pressed to obtain YOF blank. During the pressing process, the temperature is kept at room temperature, the pressure range is 100Mpa~200Mpa, and the pressing time is kept at 24h~48h. For example, 48h can obtain higher density.

[0069] Sintering step: The YOF blank is sintered in a vacuum environment using a laser as a heat source to obtain the transparent yttrium-based sintered body; wherein the laser intensity is 100 W / cm². 2 ~200W / cm 2 The vacuum level in the vacuum environment is 10. -4 MPa ~ 10 -5 The sintering time is 5-8 hours, preferably 8 hours, at MPa, which makes it easier to obtain a single-crystal transparent yttrium-based sintered body. The longer the time, the higher the efficiency of grain boundary elimination between grains. For sintering materials that are difficult to complete in conventional sintering furnaces, the laser vacuum sintering method has unique advantages: due to the concentrated laser beam and low penetration ability, it is suitable for sintering small-area, thin-sheet products, and it is easy to sinter powders or thin-sheet compacts with different compositions from the matrix together.

[0070] The prepared transparent yttrium-based sintered body has a light transmittance of not less than 95% and a surface roughness of 0.05 μm to 0.1 μm. In some embodiments, the transparent yttrium-based sintered body is a transparent yttrium oxide ceramic, and the density of the transparent yttrium oxide ceramic is not less than 99%.

[0071] Transparent yttrium-based powder is used as the raw material, and the powder is directly sintered to obtain a transparent yttrium-based sintered body. This sintered body is then used as the component body, with the entire surface of the component body made of the transparent yttrium-based sintered body material. The excellent properties of the transparent yttrium-based sintered body give the component body strong corrosion resistance. The transparent yttrium-based sintered body has the following advantages compared to conventionally sintered yttrium-based sintered bodies:

[0072] (1) Optical transmittance: Transparent yttrium-based sintered bodies have a wide range of optical transmittance from ultraviolet and visible light to mid-infrared wavelengths. Their transmittance performance is better than that of ordinary yttrium-based sintered bodies. Ultraviolet radiation generated under plasma operating conditions can usually damage the coating, while transparent yttrium-based sintered bodies can avoid radiation damage.

[0073] (2) Mechanical properties: Transparent yttrium-based sintered bodies usually have better mechanical properties, such as high strength and high hardness. This is due to the high densification achieved during the sintering process, which reduces the generation of internal pores and defects, enabling transparent yttrium-based sintered bodies to withstand complex mechanical stresses.

[0074] (3) High temperature resistance: Transparent yttrium-based sintered bodies have high melting point and low coefficient of thermal expansion, and can maintain stable performance even in high temperature environments.

[0075] (4) Corrosion resistance: Transparent yttrium-based sintered bodies exhibit excellent corrosion resistance and can resist the long-term effects of chemical erosion and environmental factors.

[0076] Step S2: Surface conductivity is applied to the upper surface of the component body to form a conductive layer.

[0077] To fabricate conductive semiconductor components, it is typically necessary to form an upper electrode on the upper surface of the component body. For example... Figure 2 As shown, the present invention performs surface conductivity on the upper surface of the component body 31 to form a metal conductive layer 32, that is, the transparent yttrium-based sintered body is combined with the metal conductive layer 32 to form a conductive component body.

[0078] In some embodiments, the surface conductivity includes applying a metal conductive layer 32 to the upper surface of the component body 31, using any one of the processes of chemical vapor deposition, physical vapor deposition, and atomic layer deposition to deposit the metal conductive layer 32. For example, the chemical vapor deposition process utilizes gaseous reactants to undergo a chemical reaction on the upper surface of the component body 31, thereby forming a solid film and gaseous byproducts. For the deposition of the metal conductive layer 32, the gaseous reactants used are organometallic compounds. Specifically, organometallic compounds, such as trimethylgallium, trimethylaluminum, and triethylarsenic, are introduced into the reaction chamber where the component body 31 is placed. Under certain temperature and pressure conditions, these organometallic compounds decompose on the upper surface of the component body 31, thereby forming the desired metal conductive layer 32.

[0079] In other embodiments, the method of forming the metal conductive layer 32 includes: implanting metal ions into the upper surface of the component body 31 to form a metal conductive layer 32 extending downward from the upper surface of the component body 31. The metal ions contain Al. 3+ Ni 3+ and Ti 3+ At least one of the following. During ion implantation, the concentration and distribution of the dopant can be precisely controlled by precisely controlling the energy and dose of the ion beam, providing a highly customized manufacturing process. Therefore, in order to form a metal conductive layer 32 of a certain thickness, the concentration of the metal ion implantation is 10E12 atoms / cm². 2 ~10E14 atoms / cm 2 The metal ions penetrate to a depth of 500 nm to 1000 nm into the component body 31, and the conductivity of the resulting conductive layer 32 is 10. -2 Ω / cm~10-3 Ω / cm. It is understood that the conductive layer 32 can not only be used as the upper electrode for conducting electricity, but its excellent conductivity can also quickly transfer heat from hot spots to other areas, thereby achieving rapid heat dissipation.

[0080] The conductive layer 32, formed by deposition technology or ion implantation, has a thickness of 500 nm to 1000 nm. When a transparent yttrium-based sintered body is combined with the conductive layer 32 to form a conductive component body, the thickness of the conductive layer 32 is usually greater than the thickness of the transparent yttrium-based sintered body. It is understood that the specific thickness of the conductive layer 32 depends on actual production requirements; if the semiconductor component being fabricated does not require high conductivity, the thickness of the conductive layer 32 can also be less than the thickness of the transparent yttrium-based sintered body.

[0081] Step S3: Drill holes in the conductive surface of the component body to form a through-hole.

[0082] Holes are drilled into the conductive surface of the component body using machining or ultrasonic drilling to form through-holes. In some embodiments, the diameter of the hole is 0.35mm to 0.37mm. Figure 3 As shown, after drilling, the surface of the component body 31 and the inner wall of the hole 33 are both transparent yttrium-based sintered bodies, which makes the semiconductor component have strong corrosion resistance under the bombardment of plasma. This avoids the need to use coating technology to deposit corrosion-resistant coatings on the surface of the component body 31 and the inner wall of the hole 33 after drilling, and avoids the problem of micro-particle contamination generated during the coating process after drilling.

[0083] In some embodiments, the method for preparing corrosion-resistant components can be used to prepare any one of the following semiconductor components: a gas spray disk, a constraint ring, and a grounding ring. It is understood that the method for preparing corrosion-resistant components provided by this invention is not limited to preparing the aforementioned semiconductor components, but is also applicable to preparing other semiconductor components that require a corrosion-resistant layer to be formed on their surface and also possess conductivity.

[0084] In some embodiments, the corrosion-resistant component is a gas spray disk, wherein the gas spray disk is composed of a transparent yttrium-based sintered body as its main body, and Al is implanted onto the upper surface of the main body of the gas spray disk using ion implantation technology. 3+ This forms a gas spray disk that serves as the upper electrode. The gas spray disk provided by this invention can be used in plasma processing devices.

[0085] Figure 4 A capacitively coupled plasma etching apparatus 100 provided in an embodiment of the present invention includes:

[0086] A reaction chamber 1 is provided inside a base 2, which is used to support the substrate w to be processed;

[0087] The gas spray disk 3 provided by the present invention has a plurality of holes 33, and is disposed opposite to the base 2 for supplying reaction gas to the reaction chamber 1; and,

[0088] At least one radio frequency source 4 is electrically connected to the gas spray disk 3 or the base 2, and is used to generate a radio frequency electric field between the gas spray disk 3 and the base 2 to dissociate the reactive gas into plasma.

[0089] It should be understood that the plasma etching apparatus in this invention can be any type of plasma etching apparatus that includes a gas spray disk, such as a capacitively coupled plasma etching apparatus. Figure 4 This is merely an example and may include fewer or more components, or the arrangement of those components may be the same as or different from that shown in the figure.

[0090] The following detailed description of a method for preparing a corrosion-resistant component provided by the present invention is based on specific embodiments.

[0091] Example

[0092] This embodiment provides a method for preparing a gas spray disk based on transparent yttrium fluoride ceramic, comprising the following steps:

[0093] Step S1: YOF powder with a grain size of 5 nm is used as a precursor for sintering transparent yttrium fluoride ceramics, and SiO2 nanospheres with a grain size of 5 nm are used as sintering aids. The YOF powder and the SiO2 nanospheres are mixed evenly, wherein the mass ratio of the YOF powder to the SiO2 nanospheres is 0.05 wt%.

[0094] Step S2: Press the mixed YOF powder and SiO2 nanospheres to obtain YOF blank. The pressure is maintained at 150 MPa and the pressing time is 48 hours. The pressing process is kept at room temperature.

[0095] Step S3: Under vacuum conditions, the YOF blank is sintered using a laser as a heat source to obtain a transparent yttrium-based sintered body. The laser intensity during the sintering process is 100 W / cm². 2 The vacuum degree is 10. -4 At MPa, sintered for 8 hours, a transparent yttrium fluoride ceramic was obtained;

[0096] Step S4: Using ion implantation technology, Al 3+ The conductive transparent yttrium fluoride ceramic is obtained by injecting Al into the upper surface of the transparent yttrium fluoride ceramic.3+ The injection concentration was 10E12 atoms / cm³ 2 Al 3+ The implantation depth was 500 nm;

[0097] In step S5, ultrasonic-assisted mechanical drilling is used to drill holes from top to bottom in the conductive transparent yttrium oxyfluoride ceramic to form a channel (i.e., a gas spray head) that penetrates the conductive transparent yttrium oxyfluoride ceramic. The diameter of the channel is 0.36 mm, and a gas spray disc based on transparent yttrium oxyfluoride ceramic is finally prepared.

[0098] Physical characterization of the conductive transparent yttrium fluoride ceramic after drilling was performed.

[0099] Comparative Example

[0100] This comparative example provides a method for preparing a gas spray disk based on a thermally sprayed yttrium fluoride oxychloride coating, comprising the following steps:

[0101] Step S1: Provide an aluminum substrate and use a drilling device to drill holes in the aluminum substrate from top to bottom to obtain a number of gas spray heads;

[0102] Step S2: Using atmospheric plasma spraying technology, yttrium oxyfluoride powder is sprayed onto an aluminum substrate through a plasma spraying device, ultimately preparing a gas spraying disk based on a thermally sprayed yttrium oxyfluoride coating.

[0103] Physical characterization of thermally sprayed yttrium fluoride coatings.

[0104] Experimental results:

[0105] (1). Results of scanning electron microscopy microscopy: such as Figure 5 As shown, under a scanning electron microscope with a magnification of 200x, the surface of conductive transparent yttrium fluoride ceramic ( Figure 5 a) is relatively flat with no obvious boundaries, but the surface of the thermally sprayed yttrium fluoride coating ( Figure 5 b) is relatively rough and has obvious boundaries.

[0106] (2). Results of scanning electron microscopy morphology: Conductive transparent yttrium oxyfluoride ceramics and thermally sprayed yttrium oxyfluoride coatings were subjected to high-temperature thermal cycling (from 25℃ to 300℃, 5 cycles), as shown in Figure 6. After high-temperature thermal cycling, the surface of the conductive transparent yttrium oxyfluoride ceramics ( Figure 6 a) No cracks appeared on the surface of the thermally sprayed yttrium fluoride coating. Figure 6 (b) shows relatively obvious cracks. It is generally believed that cracks are the source of pollutant particles. Especially at the moment the cracks form, tiny particulate pollutants will fall out.

[0107] (3) Results of etching rates on the etched surfaces: The etching rates of the etched surfaces of conductive transparent yttrium oxyfluoride ceramics and thermally sprayed yttrium oxyfluoride coatings were statistically analyzed, such as... Figure 7 As shown, where, Figure 7 In the diagram, A represents a thermally sprayed yttrium oxyfluoride coating, and B represents a conductive transparent yttrium oxyfluoride ceramic. The average etching rate of the etched surface of the thermally sprayed yttrium oxyfluoride coating is 4.54 nm / h, while the average etching rate of the etched surface of the conductive transparent yttrium oxyfluoride ceramic is 1.02 nm / h. This indicates that the etched surface of the thermally sprayed yttrium oxyfluoride coating has a faster rate of material removal per unit time, while the etched surface of the conductive transparent yttrium oxyfluoride ceramic has a slower rate of material removal per unit time. In other words, the corrosion resistance of the conductive transparent yttrium oxyfluoride ceramic is stronger than that of the thermally sprayed yttrium oxyfluoride coating.

[0108] (4) Results of crystal plane orientation; X-ray diffraction (XRD) was used to analyze the crystal structure and crystal plane orientation of conductive transparent yttrium fluoride ceramics, such as... Figure 8 As shown, the crystal exhibits stronger intensity at specific diffraction peaks, indicating that the conductive transparent yttrium fluoride ceramic has a highly preferred orientation (440) crystal plane. This means that certain specific crystal planes are more prominent or dominant than others, implying that the distribution of these crystal planes in the material's microstructure is more uniform and consistent than other crystal planes, without localized differences in crystal plane orientation, thus ensuring the uniformity of the entire material structure. Due to the consistency of the preferred orientation, the etching process ensures a consistent etching rate across the etched surfaces of the conductive transparent yttrium fluoride ceramic, preventing the formation of microparticles due to excessively fast etching rates on certain crystal planes.

[0109] In summary, this invention uses a transparent yttrium-based sintered body to fabricate the component body. The upper surface of the component body is then made conductive to form a conductive layer. The transparent yttrium-based sintered body and the conductive layer are then combined to prepare a conductive component body. Finally, holes are drilled into the conductive component body to form through-holes. This ensures that both before and after drilling, the surface of the component body and the inner walls of the holes are made of a transparent yttrium-based sintered body with high light transmittance, high density, and good corrosion resistance. Therefore, it eliminates the need for additional coating on the surface of the component body and the inner walls of the holes after drilling to form a corrosion-resistant coating, significantly reducing the generation of microparticles.

[0110] Although the present invention has been described in detail through the preferred embodiments above, it should be understood that the above description should not be considered as a limitation of the present invention. Various modifications and substitutions to the present invention will be apparent to those skilled in the art after reading the above description. Therefore, the scope of protection of the present invention should be defined by the appended claims.

Claims

1. A method for producing a corrosion-resistant component, characterized by, The application relates to a transparent yttrium-based sintered body and a corrosion-resistant component made of the transparent yttrium-based sintered body. The application provides a component body made of a transparent yttrium-based sintered body; The upper surface of the component body is surface-conducting to form a conductive layer; The surface-conducting component body is punched to form a hole penetrating through the component.

2. The production method according to claim 1, wherein The surface-conducting includes applying a metal conductive layer on the upper surface of the component body.

3. The production method according to claim 1, wherein The surface-conducting includes metal ion implantation on the upper surface of the component body to form a metal conductive layer extending downward from the upper surface of the component body.

4. The production method according to claim 3, wherein The metal ions comprise at least one of Al 3+ , Ni 3+ , and Ti 3+ .

5. The production method according to claim 3, wherein The concentration of the metal ion implant is 10E12 atoms / cm 2 ~ 10E14 atoms / cm 2 .

6. The production method according to claim 1, wherein The thickness of the conductive layer is 500nm-1000nm.

7. The production method according to claim 1, wherein The conductivity of the conductive layer is 10 -2 Ω / cm ~ 10 -3 Ω / cm.

8. The production method according to claim 1, wherein The transparent yttrium-based sintered body includes at least one of transparent yttrium oxide sintered body, transparent yttrium oxyfluoride sintered body and transparent yttrium fluoride sintered body.

9. The production method according to claim 1, wherein The light transmittance of the transparent yttrium-based sintered body is not less than 95%.

10. The production method according to claim 1, wherein The surface roughness of the transparent yttrium-based sintered body is 0.05-0.1 micron.

11. The production method according to claim 1, wherein The preparation method of the transparent yttrium-based sintered body includes: The mixing step: taking yttrium-containing powder as a precursor and silica nanospheres as a sintering aid, and mixing the yttrium-containing powder and the silica nanospheres uniformly; The forming step: pressing the mixed yttrium-containing powder and silica nanospheres to obtain a powder compact, the pressure is 100-200MPa, and the pressing time is 24-48 hours; Sintering step: sintering the powder compact under vacuum environment by using laser as heat source, and obtaining the transparent yttrium-based sintered body, the intensity of the laser is 100 W / cm 2 ~200 W / cm 2 , the vacuum degree of the vacuum environment is 10 -4 Mpa~10 -5 Mpa, and the sintering time is 5h~8h.

12. The production method according to claim 11, wherein In the mixing step, the grain size of the yttrium-containing powder is 5-20nm.

13. The production method according to claim 11, wherein In the mixing step, the mass ratio of the yttrium-containing powder to the silica nanospheres is 0.05wt%-0.1wt%.

14. The production method according to claim 11, wherein The transparent yttrium-based sintered body is selected from transparent yttrium-based ceramics.

15. The production method according to claim 14, wherein The transparent yttrium-based ceramics have a density not less than 99%.

16. A corrosion resistant component, characterized by The application relates to a transparent yttrium-based sintered body and a corrosion-resistant component made of the transparent yttrium-based sintered body. The application provides a component body made of a transparent yttrium-based sintered body; The upper surface of the component body is surface-conducting to form a conductive layer; The surface-conducting component body is punched to form a hole penetrating through the component. The surface-conducting includes applying a metal conductive layer on the upper surface of the component body.

17. The corrosion-resistant component of claim 16, wherein The surface-conducting includes metal ion implantation on the upper surface of the component body to form a metal conductive layer extending downward from the upper surface of the component body.

18. The corrosion-resistant component of claim 16, wherein The thickness of the conductive layer is 500nm-1000nm.

19. The corrosion-resistant component of claim 16, wherein The transparent yttrium-based sintered body includes at least one of transparent yttrium oxide sintered body, transparent yttrium oxyfluoride sintered body and transparent yttrium fluoride sintered body.

20. The corrosion-resistant component of claim 16, wherein The light transmittance of the transparent yttrium-based sintered body is not less than 95%.

21. A plasma processing apparatus, characterized by, The surface roughness of the transparent yttrium-based sintered body is 0.05-0.1 micron.

22. The plasma processing apparatus of claim 21, wherein, The preparation method of the transparent yttrium-based sintered body includes: The mixing step: taking yttrium-containing powder as a precursor and silica nanospheres as a sintering aid, and mixing the yttrium-containing powder and the silica nanospheres uniformly; The forming step: pressing the mixed yttrium-containing powder and silica nanospheres to obtain a powder compact, the pressure is 100-200MPa, and the pressing time is 24-48 hours; In the mixing step, the grain size of the yttrium-containing powder is 5-20nm. In the mixing step, the mass ratio of the yttrium-containing powder to the silica nanospheres is 0.05wt%-0.1wt%. The transparent yttrium-based sintered body is selected from transparent yttrium-based ceramics. The transparent yttrium-based ceramics have a density not less than 99%. The application relates to a transparent yttrium-based sintered body and a corrosion-resistant component made of the transparent yttrium-based sintered body. The application provides a component body made of a transparent yttrium-based sintered body; The upper surface of the component body is surface-conducting to form a conductive layer; The surface-conducting component body is punched to form a hole penetrating through the component. The surface-conducting includes applying a metal conductive layer on the upper surface of the component body. The surface-conducting includes metal ion implantation on the upper surface of the component body to form a metal conductive layer extending downward from the upper surface of the component body. The thickness of the conductive layer is 500nm-1000nm. The transparent yttrium-based sintered body includes at least one of transparent yttrium oxide sintered body, transparent yttrium oxyfluoride sintered body and transparent yttrium fluoride sintered body. The corrosion-resistant component includes any one of a gas spraying disc, a confinement ring and a grounding ring. The plasma processing device includes the corrosion-resistant component according to any one of claims 16-20. The plasma processing device is an inductively coupled plasma etching device or a capacitively coupled plasma etching device.